2021
DOI: 10.1158/0008-5472.can-21-0184
|View full text |Cite
|
Sign up to set email alerts
|

EPHB2 Activates β-Catenin to Enhance Cancer Stem Cell Properties and Drive Sorafenib Resistance in Hepatocellular Carcinoma

Abstract: The survival benefit derived from sorafenib treatment for patients with hepatocellular carcinoma (HCC) is modest due to acquired resistance. Targeting cancer stem cells (CSC) is a possible way to reverse drug resistance, however, inhibitors that specifically target liver CSCs are limited. In this study, we established two sorafenib-resistant, patient-derived tumor xenografts (PDX) that mimicked development of acquired resistance to sorafenib in patients with HCC. RNA-sequencing analysis of sorafenib-resistant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…In the established ceRNA networks, the 22 DEmRNAs attracted the researchers' attention, and they found that they were effective regulators during cancer progression [ 43 49 ]. EPHB2 has been associated with cancer stemness and acquired sorafenib resistance via the β -catenin/TCF1 axis [ 43 ]. CXCL5 as a tumor angiogenic factor promoted the expression of FOXD1 by activating the AKT/NF- κ B pathway in colorectal cancer [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the established ceRNA networks, the 22 DEmRNAs attracted the researchers' attention, and they found that they were effective regulators during cancer progression [ 43 49 ]. EPHB2 has been associated with cancer stemness and acquired sorafenib resistance via the β -catenin/TCF1 axis [ 43 ]. CXCL5 as a tumor angiogenic factor promoted the expression of FOXD1 by activating the AKT/NF- κ B pathway in colorectal cancer [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have verified that EphB2 is abnormally expressed in many cancer types Table 1 . EphB2 is overexpressed in most tumors, such as hepatocellular carcinoma, breast cancer, glioma, and malignant mesothelioma ( Leung et al, 2021 ; Wu et al, 2004 ; Nakada et al, 2004 ; Goparaju et al, 2013 ), and it functions as a tumor promoter. However, the expression of EphB2 is low in other tumors, such as colorectal cancer and bladder cancer ( Xi et al, 2012 ; Lee et al, 2021 ), indicating that it exerts a tumor-suppression effect.…”
Section: Ephb2 In Various Human Tumorsmentioning
confidence: 99%
“…It is widely known that Eph receptors have essential roles in embryonic development, and in the past decade their critical roles in the occurrence and progression of human disease, especially in tumorigenesis, have become more and more clear ( Pasquale, 2008 ; Xi et al, 2012 ; Husa et al, 2016 ). Undoubtedly, enriching our understanding of the roles Eph receptors play in the potential biomarkers, stemness, and drug resistance of cancer will provide new opportunities for tumor therapy ( Pasquale, 2010 ; Leung et al, 2021 ). Eph receptor B2 (EphB2) has been demonstrated to play a crucial modulatory role in tumor progression ( Guo et al, 2006 ; Lam et al, 2014 ; Buckens et al, 2020 ; Morales et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, AKT and MAPK have emerged as critical players in the sorafenib resistance process [61,62]. Of note, enhancing cancer stem cell properties also promoted sorafenib resistance in HCC [63]. In addition to that, HIF-1α/VEGF pathway adapted HCC cells to hypoxic microenvironment and blunted the antiangiogenic actions of sorafenib [64].…”
Section: Discussionmentioning
confidence: 99%